A new virtual oscillator control for synchronization of single-phase parallel inverters in islanded microgrid. Issue 4 (21st December 2022) - Gurugubelli, Vikash; Ghosh, Arnab; Panda, Anup Kumar
ABSTRACT: This paper describes the concept of virtual oscillator control (VOC) for parallel-connected single-phase inverters (SPIs). The principal idea is to introduce a series of weakly coupled oscillators (Deadzone oscillator-based VOC and Van der Pol oscillator-based VOC) that can be used for the regulation of single-phase power inverters in an islanded microgrid (MG). Its dynamic equations are used to provide the frequency and amplitude references of the inverters. In these traditional methods, there is always the presence of a 3 − order harmonic in the output voltage, which causes a significant amount of 3 − order harmonic current in the system. The non-linear dynamical equations of the oscillator are analyzed and its non-linear current source (NCS) is made simpler in order to develop new VOC for SPIs that can effectively get rid of the 3 − order harmonic component in the oscillator's output voltage. Finally, an extensive comparison of Deadzone-based VOC (Dz-VOC), Van der pol-based VOC (VdP-VOC), and new VOC-based controllers with linear and nonlinear loads is presented. The new VOC-based controller minimizes the 3-order harmonic component in the output voltage and achieves a quicker response compared to the conventional VdP-VOC-based controller. Simulation results of the Dz-VOC, VdP-VOC, and proposed new VOC-based control methods with different loads (Resistive, Linear RLC, non-linear) were compared and analyzed in detail. The total harmonic distortion (THD) of the current in Dz-VOC, VdP-VOC, and new VOC are 1.98%, 1.11%, and 0.21%, respectively. The 3 rd harmonic is dominant in both Dz and VdP VOCs, while in the new VOC the 3 rd harmonic is very less and below 0.1%. The new VOC is also showing good current sharing and fast voltage synchronization (within 0.2 s). Hardware experimentation is also carried out to analyze the efficacy of the proposed new VOC controlled SPI in standalone MG. The results clearly depict that the new VOC control strategy is quite efficient in handling the output voltage harmonics and situations of different loadings in the standalone MG.